Strategy of islamic boarding school-based in facing the era of revolution 4.0 towards the era of society 5.0 - Mukarromah, Aenullael; Nur, Mujiburrahman; Banqitoh, Ali Salim (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This research is motivated by the importance of Islamic boarding school based education in Madrasah Ibtidaiyah to safeguard the next generation from the influence of globalization and the revolutionary era, and also as a platform for preparing them with knowledge of both religious and general subjects. Madrasah Ibtidaiyah is an education level equivalent to Elementary School in an Islamic Educational Institution, where the learning process is conducted formally and instills strong Islamic values. Madrasah Ibtidaiyah NWDI Nurul Haramain is one of the Islamic boarding school based schools whose presence can address parental concerns about moral disruption and technological advancements in the globally revolutionary era. The aim of this research is to investigate the development of Islamic boarding school based madrasah as an effort to face the challenges of the era 4.0 towards the era of society 5.0 at MI NWDI Nurul Haramain, marked by rapid and transformative technological advancements that require educational institutions like madrasah to adapt to various changes to remain relevant and effective. The researchers utilized a descriptive qualitative approach in conducting the research. Data was collected through non-participative observation, documentation, and interviews to gain a comprehensive understanding of the current situation of the madrasah and the challenges faced in confronting the era 4.0 towards the era of society 5.0. Data analysis employed the techniques of Miles and Huberman, focusing on data reduction, data presentation, and drawing conclusions. The research findings indicate that MI Nurul Haramain; 1) prepares madrasah teachers to possess digital skills, creative thinking, innovativeness, dynamism, and Quran memorization as a reinforcement, 2) conducts both intracurricular and extracurricular activities for students, and 3) integrates technology as a tool for teaching and learning activities.